Language and religion in Tudor Cornwall: the testimony of Sacrament an Alter - Harvey, Anthony (Studia Celtica Posnaniensia, 2024)
This article is centred around a detailed review of D.H. Frost’s new (2023) critical edition and translation of the Cornish and Latin text Sacrament an Alter, in both its theological/historical and its philological/linguistic aspects. First, Dr Frost’s exposition of his text’s remarkable background is placed against the constantly changing character of official Tudor ideology, and the ecclesiological lens through which he views his material discussed. Points from his linguistic analysis (including revivalist reconstructions) are then examined and, prompted by Frost’s portrayal of the state of Cornish-language literacy in the last quarter of the sixteenth century, similarities are adduced with the known situation of near-contemporary Manx Gaelic. Traditional Cornish went into ultimately terminal decline, but Manx went on to receive both the Prayer Book and the Bible in translation; Cornwall’s disadvantage in not constituting a diocese in its own right is suggested as a significant factor in the contrasting fates of the two small Celtic languages in question. Finally, attention is drawn to the potentially striking efficacy of small networks of dedicated scholars, whatever their time and place.